Needs Analysis for Developing Google Sites-Based Character Education Media Enhanced with Augmented Reality Using Problem-Based Learning in Indonesian Elementary Schools - Tri Sari Yanti; Makmum Raharjo; Syarifuddin Syarifuddin (Journal of Innovation and Research in Primary Education, 2026)
Character education in elementary schools faces significant challenges in the digital era, including declining student engagement with conventional teaching methods and inadequate integration of character values into curricula. This study aimed to analyze the needs for developing Google Sites-based character education media enhanced with Augmented Reality technology using the Problem-Based Learning approach in Indonesian elementary schools. A quantitative descriptive design with needs analysis was employed, utilizing structured questionnaires distributed to two fifth-grade teachers and 30 fifth-grade students selected through purposive sampling. Data were analyzed using descriptive statistics with percentage calculations and mean score computations across five dimensions: pedagogical, technical, cognitive, aesthetic, and evaluative. Results revealed remarkably high need indicators, with students averaging 94.4% and teachers 90.4% across all dimensions. Students demonstrated universal preference for interactive, visually appealing media with immediate feedback mechanisms, while teachers emphasized sustained professional development needs and embedded assessment tools. These findings validate the critical necessity for integrating technological affordances, pedagogical frameworks, and authentic problem-solving contexts in character education. The study extends the TPACK framework to character education domains and provides evidence-based design specifications for developing innovative, stakeholder-centered learning media that addresses contemporary educational demands in elementary settings.